30th Annual IEEE Power Electronics Specialists Conference. Record. (Cat. No.99CH36321)
DOI: 10.1109/pesc.1999.785588
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of three-phase rectifiers with constant-voltage loads

Abstract: This brief presents a quantitative analysis of the operating characteristics of three-phase diode bridge rectifiers with ac-side reactance and constant-voltage loads. We focus on the case where the ac-side currents vary continuously (continuous ac-side conduction mode). This operating mode is of particular importance in alternators and generators, for example. Simple approximate expressions are derived for the line and output current characteristics as well as the input power factor. Expressions describing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 6 publications
0
44
0
Order By: Relevance
“…Later, Jahns et al [9], [11] performed a detailed study of this effect. They showed that for analysis purposes, the dc voltage source in Fig.…”
Section: Uncontrolled Generationmentioning
confidence: 99%
“…Later, Jahns et al [9], [11] performed a detailed study of this effect. They showed that for analysis purposes, the dc voltage source in Fig.…”
Section: Uncontrolled Generationmentioning
confidence: 99%
“…The thévenin equivalent circuit of three thyristor rectifiers and diode rectifiers have been presented in [27] and [28] respectively. The equivalent circuit presented in [27] provides some scope for improvement during the initial transient period of the DC fault current, whereas [28] presents a representation of the DC side on the input AC side. The paper formally proposes and presents a thévenin equivalent model of the VSC and the three phase anti-parallel diode rectifier for fault studies in DC systems.…”
Section: Introductionmentioning
confidence: 99%
“…2(b)], or simplified even further by treating the rectifier and voltage source as a three-phase resistive load [see Fig. 2(c)], [6]. It is helpful to consider the voltage versus current characteristics (VI loci) of an IPM machine operating with a three-phase resistive load.…”
Section: A Voltage-current Loci Of Ipm Machinesmentioning
confidence: 99%
“…The dc measurements should give a better indication of the output power delivered to the voltage source load during UCG. The calculated dc voltage and current curves were obtained by scaling the calculated ac voltage and current curves by the factors 1.355 for current (theoretical ratio of rectified dc to the rms ac phase current) and 1.283 for voltage [4], [6].…”
Section: Voltage-current and Voltage-power Loci With Rectifier Andmentioning
confidence: 99%